The Media and Development : What's the Story? - Locksley, Gareth (World Bank, 2012)
This paper assesses the impact the media have on the development process. Because the media can be used and delivered in so many ways, there is no single means of analyzing its contributions to development. Thus, the paper presents a range of storylines with the common thread being the media's role in development. The paper also discusses older and newer trends in the relationship between the media and development, and how they might impact developing countries.